2011
DOI: 10.1159/000330114
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the 2010 Nutritional Objectives for the Spanish Population in the Balearic Islands’ Adolescents

Abstract: Aims: To assess compliance with the 2010 nutritional objectives for the Spanish population in the Balearic Islands’ adolescents. Methods: A cross-sectional nutrition survey was carried out in adolescents (n = 1,231). Dietary habits were assessed by means of 2 nonconsecutive 24-hour recalls and a semiquantitative food frequency questionnaire. Differences in the percentage of compliers with the 2010 nutritional objectives and differences in food consumption patterns between genders and high or low consumers of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
3
1
0
2
Order By: Relevance
“…In the MD the main source of fat intake is olive oil, which is low in saturated and n-6 fatty acids but high in plant monounsaturated fat (72) . In line with this, we found that intake of n-6 fatty acids was low in FF consumers with low and also high adherence to the MD; however, intake was lower than RDI value (73) . In addition to n-6 fatty acids, intake of n-3 fatty acids was inadequate in FF consumers with high adherence to the MD.…”
Section: Discussionsupporting
confidence: 85%
“…In the MD the main source of fat intake is olive oil, which is low in saturated and n-6 fatty acids but high in plant monounsaturated fat (72) . In line with this, we found that intake of n-6 fatty acids was low in FF consumers with low and also high adherence to the MD; however, intake was lower than RDI value (73) . In addition to n-6 fatty acids, intake of n-3 fatty acids was inadequate in FF consumers with high adherence to the MD.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, because of the higher prices, the lack of economic support provided to families, and the tastelessness of gluten-free products celiac patients may tend to consume other products that are richer in lipids and/or protein such as eggs, meat, fish, and sweetened beverages instead of gluten-free substitute products (22). Consistent with other studies (10,11,15), participants with CD consumed less fiber, although the differences between groups were not statistically significant, and both groups were under the national nutritional recommendation as observed in other healthy cohorts using the same age categories (23). This in part can be explained because gluten-free cereals tend to have lower amounts of dietary fiber, and subjects with CD have a low intake of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 77%
“…A pattern of healthy eating habits and adequate physical activity during adolescence reduces the risk of major chronic diseases [ 4 - 6 ]. However, a high intake of total fat, saturated fat and sodium, a low intake of vitamins and minerals, and a low consumption of fruits and vegetables are usual dietary patterns among adolescents [ 7 - 9 ], and only a small proportion of the Balearic Islands’ adolescents met the requirements of dietary fibre, folate, iodine, total fat, saturated fat, polyunsaturated fatty acid, total carbohydrate, and fruit and vegetables [ 10 ].…”
Section: Introductionmentioning
confidence: 99%